Integrated Assessment of Yield, Nitrogen Use Efficiency, and Environmental Impact of Biochar and Organic Fertilizer in Cherry Tomato Production - Zhaojie Li; Shuxin Zhang; Farooq Shah; Li Xiong; Wei Wu (Agronomy)
Chemical nitrogen (N) fertilizer application has substantially boosted crop yield over the past few decades. However, an excessive N supply often comes at the expense of soil health and the long-term sustainability of agricultural ecosystems. To avoid these concerns, both biochar and organic fertilizers offer the potential to improve soil fertility while reducing reliance on chemical N fertilizer. However, the impact of these amendments on N use efficiency (NUE) and potential environmental risk in cherry tomatoes remains unclear. To fill the void, a two-year field experiment was conducted to evaluate the effects of biochar and organic fertilizer in combination with chemical N fertilizer on cherry tomato fruit yield, N uptake, NUE, and potential environmental risk. The results showed that compared with the CK (without biochar and organic fertilizer), biochar application had no significant effect on cherry tomato yield and NUE. In contrast, compared to CK, organic fertilizer increased the fruit yield, partial factor productivity of applied N, N agronomic efficiency, and N recovery efficiency by 21.4%, 18.4%, 18.5%, and 25.1%, respectively, averaged across both cropping seasons. In addition, increasing N fertilizer application alongside organic fertilizer further enhanced cherry tomato yield, but it compromised NUE and increased potential environmental risks related to global warming and terrestrial acidification. A comprehensive evaluation using Z-score analysis, integrating yield performance, NUE, and environmental risk, identified the combined application of organic fertilizer and 160 kg N ha−1 as the most promising fertilizer management practice for the sustainable production of cherry tomatoes. These findings provide a valuable reference for optimizing fertilizer management in cherry tomato production, especially in tropical regions where achieving a balance between sustainability and productivity is crucial.